1997
DOI: 10.1097/00005537-199704000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Clinical Features of Sensorineural Hearing Loss Associated With the 1555 Mitochondrial Mutation

Abstract: Five Japanese families showing aminoglycoside-induced hearing loss were genetically as well as clinically investigated. A mitochondrial mutation at nucleotide 1555 was found in 28 out of 32 subjects. One hundred American control subjects did not show any evidence of the mutation at nucleotide 1555, suggesting that the 1555 A-->G (A1555G) mitochondrial mutation may be found more frequently among populations in the Asian continent. Many subjects who harbor this mitochondrial mutation exhibit a mild, high-frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
101
2
5

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(115 citation statements)
references
References 15 publications
(21 reference statements)
7
101
2
5
Order By: Relevance
“…We found 1555A > G at a frequency of 2.6% in the cohort, and the fact that only case reports have previously been published on this mutation likewise suggests that it is rare among patients with SNHI. 4,8,9 In contrast, every patient with matrilineal hearing impairment in a Spanish cohort was found to harbour 1555A > G. 10 The discrepancy in the observed frequencies may be explained by several factors. Firstly, ascertainment bias may be involved, 16 as our results are based on patients detected in population-based registers, while the patients reported by Estivill et al 10 were selected from several clinical centres or were obtained through advertisements in the public media.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We found 1555A > G at a frequency of 2.6% in the cohort, and the fact that only case reports have previously been published on this mutation likewise suggests that it is rare among patients with SNHI. 4,8,9 In contrast, every patient with matrilineal hearing impairment in a Spanish cohort was found to harbour 1555A > G. 10 The discrepancy in the observed frequencies may be explained by several factors. Firstly, ascertainment bias may be involved, 16 as our results are based on patients detected in population-based registers, while the patients reported by Estivill et al 10 were selected from several clinical centres or were obtained through advertisements in the public media.…”
Section: Discussionmentioning
confidence: 93%
“…The mutation 1555A > G was the first to be identified, 4 and interestingly, it also appears to confer an increased risk of hearing impairment in conjunction with the use of aminoglycosides. 4 The mutations 7445A > A and 7472insC have been reported only in selected families [5][6][7] and 1555A > G in small series of cases 4,8,9 except for a recent study, where a very high frequency of 1555A > G has been observed among Spanish families with maternally inherited sensorineural hearing impairment. 10 In order to study the prevalence of these mtDNA mutations among patients with SNHI we identified cases by reviewing registers at the audiological units serving a specific population and collected cases that fulfilled certain criteria including family history data.…”
Section: Introductionmentioning
confidence: 98%
“…The mutation was absent in each of 100 American (Usami et al 1997), 400 Mongolian (Pandya et al 1997), and 414 ethnically diverse subjects (Hutchin et al 1993). Of patients with aminoglycoside-induced deafness, all patients from 12 Spanish families who had received aminoglycosides (Estivill et al 1998), 28 of 32 subjects from 5 Japanese families with a history of aminoglycoside-induced hearing loss (Usami et al 1997), yet only 7 of 41 American patients with aminoglycoside-induced hearing loss were found to possess the mutation. These findings have raised the suggestion that the mutation is more frequently encountered in Asian populations.…”
Section: Introductionmentioning
confidence: 97%
“…24,25 A study in 32 Asians with hearing loss and in 100 American controls (63 deaf and 37 normal-hearing) found the A1555G mutation in 87.5% of Asians that were deaf, and in none of the subjects in the control group, concluding that the mutation is not prevalent in non-Asian populations. 25 This results has been confirmed in a study done in Greece, in which the mutation was absent in 106 cases, 26 and in another study involving 202 early onset non-syndromic hearing loss patients in the United Kingdom.5 Likewise in our study, the A1555G mitochondrial mutation was not found in the HLG groups (consisting of group I: 13 index cases that had taken aminoglycosides, and group II: 14 index cases that had no prior use of aminoglycosides) and in the control group (100 neonates with normal otoacoustic emissions tests). These results demonstrate that the mutation was not a common cause of hearing loss in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…12 Although the number of cases in both groups was different from the number in some published studies, and although the mutation was not found in both groups (HLG and control groups), we were able to confirm the results of studies that also did not find the mutation in non-Asian or Arab ethnic groups. [24][25][26][27][28][29] There is a single study in Brazil reporting the findings of five families with hearing loss cases in which the prevalence of the mutation was 2% (4 cases). Only one of these positive cases was associated with an assumed aminoglycoside exposure; no mutation was found in the control group composed by black, white or Asian (Japanese or Chinese) ethnic groups.…”
Section: Discussionmentioning
confidence: 99%